Efeito dos óxidos de nitrogênio e de enxofre na corrosão de cobre e zinco: Um experimento para o ensino da corrosão - Vaz, Ednilson L. S. [UNESP]; Codaro, Eduardo N. [UNESP]; Acciari, Heloisa A. [UNESP] (My University, 2013)
This paper proposes a didactic experience on the simulation of the atmospheric corrosion of copper and zinc due to the presence of sulfur and nitrogen oxides. Quantitative parameters of corrosion such as gain and loss of mass were determined to assess the variation of the layer thickness of the metal and of the corrosion products. This proposal aims a better understanding of some basic aspects of acid rain formation using fundamental concepts of chemistry such as the reactivity of gases.
Effect of nitrogen and sulfur oxides on copper and zinc corrosion: An experiment for teaching of corrosion
Keywords: Atmospheric corrosion; Chemistry teaching; Nitrogen oxides; Sulfur oxides